Digitalization of Riau Malay Dance through the Rentak Bulian Dance Adventure Game as Cultural Education Medium - Syefriani, Syefriani; Setiawan, Panji Rachmat (Lectura : Jurnal Pendidikan, 2025)
Culture is an important heritage that must be preserved, including traditional arts such as the Riau Malay Dance, particularly the Rentak Bulian dance. This dance originates from the healing rituals of the Talang Mamak community in Indragiri Hulu, Riau Province. This study aims to develop an adventure game based on the Rentak Bulian dance as an interactive and engaging cultural education medium for the younger generation, focusing on the gaps in cultural education that result in a lack of understanding and appreciation for this dance. A qualitative ethnographic method was employed to gain an in-depth understanding of the cultural values and movements of the Rentak Bulian dance, while the Game Development Life Cycle (GDLC) method was applied to develop an Android-based game. These two methods complement each other throughout the development phases, where ethnography provides the necessary cultural context for game design, while GDLC ensures that these elements are effectively integrated into a digital format. The results of the study indicated that the developed game successfully integrates historical aspects, dance movements, and traditional music into an interactive digital format. This game was equipped with dance tutorials, educational quizzes, and adventure missions that can enhance learning motivation and user engagement. In short, the digitalization of traditional dance through this adventure game not only strengthens local cultural identity but also increases cultural awareness among the younger generation in the digital era.